Bactericidal synergism between antibiotics and phage endolysin Cpl-711 to kill multidrug-resistant pneumococcus. (September 2018) - Letrado, Patricia; Corsini, Bruno; Díez-Martínez, Roberto; Bustamante, Noemí; Yuste, José E.; García, Pedro
Aim: To test the synergistic effect of Cpl-711 endolysin and antibiotics for antipneumococcal activity.Materials & methods: A combination of Cpl-711 and different antibiotics (amoxicillin, cefotaxime, levofloxacin and vancomycin) was tested in a checkerboard assay against several multidrug-resistant Streptococcus pneumoniae strains. Mouse and zebrafish models of pneumococcal sepsis were used to confirm the in vitro data.Results: The activity of Cpl-711 combined with amoxicillin or cefotaxime was synergistic in the bactericidal effect against a serotype 23F multiresistant clinical isolate of S. pneumoniae . Synergy between Cpl-711 and cefotaxime was validated using both mouse and zebrafish models.Conclusion: Combination of Cpl-711 and cefotaxime may help in the treatment of diseases caused by multiresistant pneumococcal strains. Graphical abstract: